2018
DOI: 10.1016/j.cell.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Biology and Clinical Implications of the 19q13 Aggressive Prostate Cancer Susceptibility Locus

Abstract: Genome-wide association studies (GWAS) have identified rs11672691 at 19q13 associated with aggressive prostate cancer (PCa). Here, we independently confirmed the finding in a cohort of 2,738 PCa patients and discovered the biological mechanism underlying this association. We found an association of the aggressive PCa-associated allele G of rs11672691 with elevated transcript levels of two biologically plausible candidate genes, PCAT19 and CEACAM21, implicated in PCa cell growth and tumor progression. Mechanist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
135
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 128 publications
(150 citation statements)
references
References 54 publications
8
135
0
Order By: Relevance
“…While previous studies have reported the regulation of a single transcription factor at a given risk locus (Guo et al, 2016;Huang et al, 2014), here, we demonstrated that two different transcription factors can converge at a single SNP locus to regulate the expression of a lncRNA. Furthermore, while we find that NKX3.1 and YY1 preferentially bind to the non-risk alleles of rs11672691 and rs887391, an independent study reported that HOXA2 preferentially binds to the risk allele of rs11672691 (Gao et al, 2018). It is therefore possible that the synergy of multiple transcription factors binding facilitate the promoter-enhancer switching.…”
Section: Discussionmentioning
confidence: 55%
“…While previous studies have reported the regulation of a single transcription factor at a given risk locus (Guo et al, 2016;Huang et al, 2014), here, we demonstrated that two different transcription factors can converge at a single SNP locus to regulate the expression of a lncRNA. Furthermore, while we find that NKX3.1 and YY1 preferentially bind to the non-risk alleles of rs11672691 and rs887391, an independent study reported that HOXA2 preferentially binds to the risk allele of rs11672691 (Gao et al, 2018). It is therefore possible that the synergy of multiple transcription factors binding facilitate the promoter-enhancer switching.…”
Section: Discussionmentioning
confidence: 55%
“…AR enhancer duplication [18,33,34] and RB1 exon 7-17 tandem duplication [106] leading to AR overexpression and RB1 protein loss respectively are relevant examples of events discovered through whole genome sequencing studies. Similarly, SNPs located in noncoding inter-or intragenic regions were shown to be associated with specific subtypes of prostate cancer and with disease aggressiveness [107][108][109][110] .…”
Section: Resultsmentioning
confidence: 99%
“…Taken together, these data provide evidence for functional contribution of rs2680700 in changing linc0597 expression or stability. However, the exact roles of these two SNPs in RA still need further exploration [45,46]. Additionally, we attempted to discover the correlations of H19 expression with their gene polymorphisms in RA patients, but still no statistically significant results were found.…”
Section: Discussionmentioning
confidence: 99%